An Advertisement for the Publication of Abridgements of the Essay concerning Human Understanding and Other Philosophical Writings, 1672-1689, ed. J.R. Milton - Major, Rafael; Minkov, Svetozar (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2022)
As many readers of Locke Studies are aware, the long-awaited publication of a scholarly edition of Locke’s published Abrégé and the transcription of an English “Epitome” of An Essay concerning Human Understanding (Essay) should be published in the near future. Both of these documents are tantalizing for aiding in the interpretation of the Essay because they are the author’s own efforts to clarify the argument and design of his great work prior to publication. This short note briefly summarizes the evidence for the superiority of the “Epitome” over the Abrégé and suggests several ways in which a clearer understanding of these documents could contribute to a more accurate reading of the Essay.